(untitled) (Proceedings of the Global Public Health Conference, 2022)
Currently the number of adolescents is estimated to be around 18% of the total world population. There is a transition from childhood to adulthood, and changes in body shape and function occur relatively quickly so that efforts are made to improve and prevent adolescent reproductive health problems. Adolescent reproductive health education is expected to be one way to prevent adolescents from facing risky sexual behavior. This study aims to determine the factors associated with reproductive health education in SMP X Bukittinggi city. This study used a cross sectional research design in April-November 2021. The sample in the study consisted of 74 students in class IX of in High School Junior X. The results of statistical analysis showed that there was a relationship between the role of peers and adolescent reproductive health education (p-value = 0.031), where the role of peers had a risk of 3.19 times on adolescent reproductive health education. Comprehensive education for students by teachers in schools is needed as well as openness between people and children as well as the positive role of peers so that adolescent reproductive health education can be understood and applied in the daily lives of adolescents. at adolescent reproductive health education can be understood and applied in the daily lives of adolescents.